STUDI OPTIMALISASI PENGOPRASIAN WADUK SEMPOR DI KECAMATAN SEMPOR UNTUK KEBUTUHAN IRIGASI - novi andhi setyo purwono (Universitas Pancasakti Tegal, 2022)
Sempor Reservoir located in Kebumen Regency's Sempor Village, Sempor District. The Sempor Reservoir was constructed in 1968 and officially opened in 1978. The Sempor Reservoir aims to drain a 6478-hectare irrigation area. The amount of sediment in the Sempor Reservoir has become a problem. According to affected people, the irrigation is not in accordance with the irrigation water consumption schedule, causing delays in the first planting season. Farmers incurred a loss due to lower harvests as a result of the above. As a reason, irrigation operations must be re-evaluated in terms of reservoir irrigation, using more recent data. This study began by secondary data from Yogyakarta's Department for the Serayu Opak River Basin. The data is analyzed to determine reservoir drainage and irrigation water requirements. The study concludes with a reservoir operation pattern simulation. It is expected that the results of the study would contribute in the development of solutions for the operating pattern of the Sempor Reservoir as an effective irrigation reservoir. The research reveals that the available flowrate for FJ Mock data generation (inflow) for the years 2020-2029 (Years 1–10). The largest available value is 14,083m3/second, and the minimum available discharge is 0.000 m3/second; the total quantity of irrigation water related to the current cropping pattern (rice, secondary crops, and coal) is 20495.129 liters/second. The simulation results for the Sempor Reservoir operating pattern from 2020 to 2029 (Years 1–10) showed a reservoir reliability of 98.75% with a failure rate of 1.25%, which is still less than the maximum period failure rate of 20%. As a conclusion, the simulation analysis of reservoir operation patterns for the next 10 years fulfilled the plan, and its function may be relied on until 2029.